(untitled) (Fiep Bulletin - online, 2014)
In physical culture that is in physical education and sport one can discern five theories of its development. These are the following theories: biocentrism, ethnocentrism, egocentrism, anthropocentrism and theo-anthropocentrism. Each of these theories of development poses their own specific view of man and his need for physical exercising. This last one, the theory of theo-anthropocentrism nurtures as a core of its philosophy a man, but not just any man but the one who has a personality-one, unique and irrepetable. This theory recognizes a man that is a Godman. It approaches a man and his personality in most tender and cautious way. That is why it takes physical exercising as giving the most nutritious food to man who needs it primarily in the form of its bodily being. Even when talking about school physical education a schoolchild’s personality is presumed to be vital, it is approached tenderly and with lots of love. Therefore the personality of any schoolchild is not to be considered as individual, a tiny atom in wider school community. Physical exercising as the most nutritious food in agoistic terms does not put in the limelight the achievement, the result and success but considers agon as an everlasting incentive for physical exercising as a continuous activity. This necessitates the existence of the theo-humanistc approach equally to curricula and extracurricula school activities and assignments, within the physical education subject and it has to have love and role model as its foundations. These are also considered to be foundations of each and every education.